Separation Axioms in Intuitionistic Fuzzy Topological Spaces - Amit Kumar Singh; Rekha Srivastava (Advances in Fuzzy Systems)
In this paper we have studied separation axioms , in an intuitionistic fuzzy topological space introduced by Coker. We also show the existence of functors and and observe that is left adjoint to .